2021
DOI: 10.3390/antiox10091334
|View full text |Cite
|
Sign up to set email alerts
|

Noble 3,4-Seco-triterpenoid Glycosides from the Fruits of Acanthopanax sessiliflorus and Their Anti-Neuroinflammatory Effects

Abstract: Acanthopanax sessiliflorus (Araliaceae) have been reported to exhibit many pharmacological activities. Our preliminary study suggested that A. sessiliflorus fruits include many bioactive 3,4-seco-triterpenoids. A. sessiliflorus fruits were extracted in aqueous EtOH and fractionated into EtOAc, n-BuOH, and H2O fractions. Repeated column chromatographies for the organic fractions led to the isolation of 3,4-seco-triterpenoid glycosides, including new compounds. Ultra-high-performance liquid chromatography (UPLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In our previous study, moracin M had anti-inflammatory effect on alveolar macrophages, but our results showed a different pattern. However, since each cell has different characteristics, different activities may appear even with the same mechanism [38]. Therefore, as in the results of this paper, it was confirmed that moracin M had no anti-inflammatory activity in BV2 and RAW264.7 cells up to the treatment concentration.…”
Section: Discussionsupporting
confidence: 79%
“…In our previous study, moracin M had anti-inflammatory effect on alveolar macrophages, but our results showed a different pattern. However, since each cell has different characteristics, different activities may appear even with the same mechanism [38]. Therefore, as in the results of this paper, it was confirmed that moracin M had no anti-inflammatory activity in BV2 and RAW264.7 cells up to the treatment concentration.…”
Section: Discussionsupporting
confidence: 79%
“…The acanthosessilioside triterpenoids are large molecules highly decorated with sugars, which improves their solubility properties, rendering them as promising preclinical candidates for further development against inflammatory and neuro-inflammatory disorders. 32 Other related steroidal glycosides with potential therapeutic value are the natural products isolated from the starfish Ogmaster capella (capelloside A, coscinasteroside B), which have been shown to reduce intracellular ROS levels in the LPS-activated murine macrophage RAW264.7 cell line, while showing little to no cytotoxicity toward normal cells at concentrations up to 100 μM, indicating the therapeutic index. 33 …”
Section: Impact Of Ros On Human Healthmentioning
confidence: 99%
“…The natural products 3,4-seco-triterpenoid glycosides, including acanthosessilioside K (a representative of their large family, compound 38 , Figure ) from Acanthopanax sessiliflorus ( Araliaceae ) fruits, have been reported to deactivate or reduce the expression of inflammation markers (NO, PGE2, TNF-α, IL-1β, IL-6, iNOS, and COX-2) in lipopolysaccharide (LPS)-activated BV2 and RAW264.7 murine cells. The acanthosessilioside triterpenoids are large molecules highly decorated with sugars, which improves their solubility properties, rendering them as promising preclinical candidates for further development against inflammatory and neuro-inflammatory disorders . Other related steroidal glycosides with potential therapeutic value are the natural products isolated from the starfish Ogmaster capella (capelloside A, coscinasteroside B), which have been shown to reduce intracellular ROS levels in the LPS-activated murine macrophage RAW264.7 cell line, while showing little to no cytotoxicity toward normal cells at concentrations up to 100 μM, indicating the therapeutic index …”
Section: Impact Of Ros On Human Healthmentioning
confidence: 99%
“…Triterpenoids and polyphenols in E. sessiliflorus have inhibited BV2 and RAW264.7 cells induced by lipopolysaccharides. These compounds effectively reduce the production of inflammatory mediators such as NO, PGE2, TNF- α , IL-1 β , and IL-6, thereby exerting potent anti-inflammatory effects [ 9 , 16 , 83 ]. Additionally, the root barks of E. sessiliflorus have been found to inhibit osteoclast differentiation activated by RANKL in bone marrow macrophages and prevent bone loss induced by ovariectomy [ 119 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…These include monoterpenoids, sesquiterpenoids, and triterpenoids, as well as simple phenylpropanoids, lignans, coumarins, flavonoids, volatile oils, organic acids and their esters, nitrogenous compounds, quinones, phenolics, and carbohydrates. Notably, triterpenoids and lignans have gained significant attention in chemical composition research due to their remarkable potential for further research and development [ 6 , 7 , 8 , 9 ]. Since its approval as a new food resource by the Ministry of Health of the People’s Republic of China in 2008, E. sessiliflorus has become the foundation for a series of health products, such as tea, concentrated solutions, and wines, continuously entering the market.…”
Section: Introductionmentioning
confidence: 99%